PROJECT BASED LEARNING TO ENHANCE CREATIVE THINKING SKILLS OF THE NON-SCIENCE STUDENTS - Yamin, Y; Permanasari, Anna; Redjeki, S; Sopandi, W (UNIVERSITAS PAKUAN, 2020)
This study was aimed to describe students' creative thinking skills in integrated science learning on the theme of water pollution using project-based learning. The method used in this study was a descriptive method. The population and sample in this study were non-science students at a university in Bogor. The instruments used in this study were tests of creative thinking skills, peer assessment and product creativity assessment rubrics. The results showed that the average test score of students' creative thinking skills was 89% (very good category). The achievement of peer assessment indicators is 87%, while the achievement of product creativity indicators is 88%. Thus, it can be concluded that project-based integrated science learning can be used to improve the creative thinking skills of non-science students